IMPLEMENTATION OF THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN CLASS VII MTS N 1 BENGKULU CITY - Diniah, Diniah; Amin, Al Fauzan; Rohimin, Rohimin; Suradi, Ahmad; Aprianti, Nefi (Conciencia, 2024)
The purpose of this study was to determine how the implementation of the Islamic Religious Education Curriculum in the Character Education Based Independent Curriculum at MTS Negeri 01 Bengkulu City, as well as effective Islamic Religious Education curriculum implementation strategies according to the needs applied in Character Education at MTS Negeri 01 Bengkulu City. The method in this study uses a descriptive qualitative research method with an approach through interviews with 32 people consisting of class VII (Seven) students of MTS Negeri 01 Bengkulu City, Islamic Religious Education subject teachers in the clumps of moral creed, hadith quran, fiqh and SKI as well as the head of Madrasah, waka curriculum and student affairs at MTS Negeri 01 Bengkulu City, It can be concluded that the Character Education-Based Islamic Religious Education curriculum is very necessary to be implemented at MTS Negeri 01 Bengkulu City because the madrasah needs broader character education so that there are no more students who behave not in accordance with religious norms and rules in Madrasah. Character education can be implemented with strategies, namely by identifying Islamic religious values, developing teaching materials, exemplary teachers, active and participatory learning, and character building through extracurricular activities.